2011
DOI: 10.1051/alr/2011120
|View full text |Cite
|
Sign up to set email alerts
|

The spatio-temporal distribution of juvenile hake (Merluccius gayi gayi) off central southern Chile (1997–2006)

Abstract: -The Chilean hake (Merluccius gayi gayi) is the predominant groundfish species inhabiting the southern Humboldt, mainly from Coquimbo (29• S) to Puerto Montt (42 • S). At present there is only limited knowledge on the spatial distribution of juveniles of this species, particularly concerning its dependence on key physical characteristics. On the basis of annual surveys carried out during austral winters from 1997 to 2006, changes in the presence of juveniles were studied using Generalized Additive Model techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…In addition, the larval stages of jack‐mackarel have been found to be distributed mainly off central Chile [ Núñez et al ., ], where they likely find the most suitable food resources in association with the fertilizing effect of some eddy types. The distribution of demersal resources, which live in the oxygen minimum zone over the shelf and slope areas off central Chile, such as the Chilean hake ( Merluccius gayi ) [ San Martín et al ., ], could probably extend their distribution to the CTZ through ITEs. Moreover, ITEs probably reach the area of the subtropical gyre in the South Pacific [ Johnson and McTaggart , 2010] and could act as a nutrient source for planktonic communities in this oligotrophic environment.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the larval stages of jack‐mackarel have been found to be distributed mainly off central Chile [ Núñez et al ., ], where they likely find the most suitable food resources in association with the fertilizing effect of some eddy types. The distribution of demersal resources, which live in the oxygen minimum zone over the shelf and slope areas off central Chile, such as the Chilean hake ( Merluccius gayi ) [ San Martín et al ., ], could probably extend their distribution to the CTZ through ITEs. Moreover, ITEs probably reach the area of the subtropical gyre in the South Pacific [ Johnson and McTaggart , 2010] and could act as a nutrient source for planktonic communities in this oligotrophic environment.…”
Section: Resultsmentioning
confidence: 99%
“…However, the average growth at age has not changed to show either an increasing or decreasing tendency (Cerna, Cubillos, & Plaza, 2013). In turn, San Martín, Cubillos, and Saavedra (2011) found that changes in the distribution of Chilean hake were also associated with environmental conditions (e.g., temperature, salinity), although these changes were also associated with the relative participation of juveniles in the stock that inhabited shallower waters. In turn, San Martín, Cubillos, and Saavedra (2011) found that changes in the distribution of Chilean hake were also associated with environmental conditions (e.g., temperature, salinity), although these changes were also associated with the relative participation of juveniles in the stock that inhabited shallower waters.…”
Section: Introductionmentioning
confidence: 99%
“…Ecologically, Neira and Arancibia (2013) linked the change in stock off central Chile more to mortality by fishing and variations in primary productivity than to the effect of predation by some species (e.g., jumbo flying squid, Dosidicus gigas). In turn, San Martín, Cubillos, and Saavedra (2011) found that changes in the distribution of Chilean hake were also associated with environmental conditions (e.g., temperature, salinity), although these changes were also associated with the relative participation of juveniles in the stock that inhabited shallower waters. Finally, according to Landaeta and Castro (2012), the decline in the stock is associated with changes in the reproductive strategies of the species, such as moving towards more coastal spawning areas in 2004 and 2005, and producing smaller eggs.…”
Section: Introductionmentioning
confidence: 99%
“…Future investigations of size selectivity might take into consideration a larger number of mesh sizes and analyse the influence of other factors such as: (i) hanging ratio (Sulaeman et al., ; Gray et al., ; Ayaz et al., ), (ii) eventual changes in the maximum girth‐length relationship produced by morphological changes due to their reproductive activity (Ehrhardt and Die, ; Holst et al., ), and (iii) demographic composition of the species due to temporal and spatial changes (San Martín et al., ).…”
Section: Discussionmentioning
confidence: 99%